Magnetic effects on surface waves in a rotating non-homogeneous half-space with grooved and impedance boundary characteristics - Anya, Augustine; Nwachioma, Christian; Ali, Hashmat (Zielona Góra: Uniwersytet Zielonogórski)
Investigation on the Mathematical modeling of waves in a rotating grooved and impedance boundary of a non-homogeneous fibre-reinforced solid half?space under the influence of magnetic field and mechanical force is envisaged. We derived analytically, the dynamical equations for the rotating grooved and impedance boundary of the non-homogeneous fibre-reinforced solid under the influence of magnetic fields and mechanical force.
Keywords: rotation; magnetic fields; non-homogeneous half space; grooved and impedance boundary; mechanical force